BERADAPTASI DENGAN PANDEMI: MENELISIK ARAH PELAYANAN GEREJA KE DEPAN - Murni Hermawaty Sitanggang (Diegesis : Jurnal Teologi, 2021)
Covid-19 pandemic's occurrence has wholly changed humankind in all aspects of life, including worship and ministry. Virtual worship has now become a part of the spiritual life of the church as God's people. Through this paper, the author wants to review the pros and cons of implementing virtual worship and then suggest how the church should improve its ministry. This research was conducted using qualitative methods of literature study by collecting various references that discuss virtual worship implementation during the pandemic. Given the pandemic has been going on for months, churches need to project digital ministry as the primary ministry program (no longer as a temporary alternative or just a complement) and be ready to engage in social services as a form of love for God and others.